The relationship between schemas and quality of life of HIV patients: Role of social connectedness as a mediator - Rabia Javed Bhatti; Samar Fahd (Institut Agama Islam Negeri Langsa, 2022)
As the AIDS epidemic has unfolded, it has caused adverse psychosocial and economic consequences, disrupting the personal and familial lives of the infected individuals and society in general. The present study attempted to study the relationship between schemas and the quality of life among HIV individuals. The study also incorporated the role of social connectedness as a mediator. For data collection, HIV patients (n = 30) were taken using convenient sampling from the specialized HIV clinic in Rahimyar Khan, Pakistan. The information was gathered using the Urdu versions of the following standardized instruments: the Schema Mode Inventory, the WHOQOL-HIV BREF, and the Social Connectedness Scale-Revised. The results showed a strong relationship between individuals’ schemas and their quality of life. Maladaptive schemas negatively predict the quality of life, while social connectedness positively predicts the quality of life, and maladaptive schemas negatively predict social connectedness. The mediation analysis established that social connectedness fully mediates the relationship between self-esteem and social anxiety. The study also provided an understanding of the positive role of social connectedness as a mediator in enhancing the quality of life of HIV patients.